The Effectiveness of Picture on Writing Skill - Mohammed, Ibrahim Q.; Rasheed, Nidham H. (Humanities Journal of University of Zakho, 2018)
Human Being can communicate orally which make them different animal communication. even if an individual is not educated he can convey what he or she wants to express clearly. it is clear from what has been mentioned previously that there is huge different between human and animal communication. both spoken and written forms communication required activation and development. Human, society, and schools are the main elements which affects the development of these forms. expert people should hold the responsibility for this issue. these skills should be developed an enjoyable style from primary stage.